Reducing Outpatient Waiting Time through Lean Healthcare Implementation at Dumai City Regional Public Hospital - Juwaidah; Erliany Syaodih; Nining Handayani (Escalate : Economics and Business Journal, 2026)
This study aims to analyze Value Added (VA), Non Value Added (NVA), and Necessary But Non Value Added (NNVA) activities, identify waste waiting, and analyze the Current State and Future State Value Stream Mapping in outpatient services at Dumai Regional General Hospital using the Lean Healthcare approach. This study employed a qualitative descriptive design involving 15 participants consisting of the head of the outpatient installation, doctors, nurses, registration officers, and outpatients. Data were collected through in-depth interviews and direct observation. Data analysis was conducted thematically using NVivo 12 Pro through coding, node analysis, and matrix coding. The results showed that Value Added activities included doctor examinations, medical consultations, medical procedures, health education, and therapy. Non Value Added activities were predominantly waiting activities, including registration queues, waiting for doctors, medical record distribution, and pharmacy services. Necessary But Non Value Added activities include BPJS verification, data validation, medical record management, and service administration. The Current State Value Stream Mapping indicated that outpatient services were still dominated by waiting activities. The Future State Value Stream Mapping proposed several improvements, including electronic queue systems, digital medical records, integrated hospital information systems, simplified patient administration, pharmacy service optimization, and additional human resources. The study concludes that Lean Healthcare can serve as a managerial approach to reduce waste waiting and improve the efficiency and quality of outpatient services.